Case Study of Studio Ghibli VS Open AI for the Proposed Revision of Indonesia Law Number 28 of 2014 Concerning Copyright - Maria, Indri; Fakrulloh, Zudan Arief (Jurnal Syntax Transformation, 2025)
The rise of generative artificial intelligence (AI) tools that transform photos into illustrations inspired by Japan’s Studio Ghibli style has ignited debates about the protection of art styles under copyright law. This situation has prompted concerns over whether Studio Ghibli could take legal action against OpenAI for issues like false advertising, trademark infringement, or unfair competition, particularly regarding the use of Ghibli’s copyrighted works in training AI models. While the Ghibli case does not directly apply to Indonesia, it raises questions about how Indonesian law could protect local artists in similar circumstances. This research aims to analyze comparative strategies for drafting government regulations in response to the challenges posed by AI, focusing on Indonesian copyright law. A normative legal approach is used, relying on library research to examine relevant legal sources and regulations. The study identifies potential gaps in current Indonesian copyright protections for digital creations influenced by AI. In conclusion, it offers recommendations for adapting Indonesian law to safeguard the rights of artists in the age of AI, drawing lessons from international cases like Studio Ghibli vs. Open AI.